UPAYA PEMERATAAN KONTRIBUSI PARIWISATA PADA PEREKONOMIAN BALI - Awirya, Agni Alam; Gunawan, Stephanie; Nurman, Putriana (Economic Faculty, Attahiriyah Islamic University, 2017)
This study aims to analyze the distribution of income from tourism activities in Bali and to identify opportunities for more equitable utilization. The survey results show that: (1) the economic impacts of tourism activities on the Balinese economy can be seen from 3 aspects: sectoral output increase, employment output, and wage/salary output, which significantly affects the performance of particular sectors. The air transport sector in Bali is becoming the sector with the biggest increase in output and the increase in revenue due to the spending of foreign tourists. Meanwhile, the trade sector enjoys the highest employment absorption. (2) There is a gap between districts/cities in the Bali region which is shown by the amount of tourism share in business turnover in Badung regency compared to other regions. (3) There is still a chance of even distribution of tourism in Bali. Efforts to build tourist destinations in the peripheral region can be one option for efforts to state tourism activities in Bali. Keywords: tourism activities, distribution of income